Combining designs of precoder and equalizer for MIMO FBMC-OQAM systems based on power allocation strategies - Doanh, Bui Quoc; Quan, Do Thanh; Hieu, Ta Chi; Hiep, Pham Thanh (International journal of electronics and communications, 2021)
The filter bank multi-carrier (FBMC) technique is hoped to become a potential candidate for advanced wireless multiple intput multiple output (MIMO) systems as the fifth generation (5G) or the sixth generation (6G) owing to its advantages. In this paper, two combining designs of precoder and equalizer for MIMO FBMC offset quadrature amplitude modulation (OQAM) systems are investigated and proposed. These designs are developed basically on power allocation strategies such as the error balance algorithm (EBA) and water-pouring algorithm (WPA). The key idea is how to address bad sub-channels in which they are strengthened with the EBA whereas some really bad sub-channels are discarded with the WPA. The proposed designs are evaluated and compared to outstanding conventional designs based on zero forcing (ZF) and minimum mean square error (MMSE) algorithms via bit error rate (BER) and throughput issues. Simulation results show that the proposed designs can improve significantly the performance of downlink spatial multiplexing systems.